Conveyor belt or competitive market: What is a railway? - Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2007)
The notion that allowing third party access to the natural monopoly, below-rail track and signalling infrastructure might induce competitive entry in above-rail train operations has been a part of European and Australian rail policy since the early 1990s. However, competition has been slow to emerge and it is useful to ask why. This paper examines railways from a number of different perspectives in an attempt to understand the limits of what policymakers might expect from a rail access regime.